A herd health and cost savings analysis for the hyperimmunization of sheep in polyclonal antibody production - Allison, Shayna (My University, 2020)
The purpose of this research project was to determine the outcome of decreasing the use of adjuvant while immunizing sheep for polyclonal antibody. To justify the change in protocol, a herd health analysis was conducted to track site reactions and a financial analysis based on Net Present Value to determine future financial benefits. For this study 199 cross bred ewe lambs were utilized for titer test analysis after 6 months of hyperimmunization with Universal Barbiturate antigen, saline, and adjuvant. The population was broken down into four protocols based on the injection ratio. These protocols, with their respective injection ratios were Current Protocol #1 (1/1/1), Current Protocol #2 (0.5/1/1), Test Protocol #1 (1/1/0.5), and Test Protocol #2 (1/1/0). In addition to the titer test, 128 sheep were randomly selected for site reaction data collection. Based on a graded scale, animals were graded based on the physical reaction sites over their lumbar regions where the injections took place. The results from both data collection methods were then compared to determine the best methods to decrease sight reactions and increase immune response rate. The results from this data compared the costs associated with adjuvant use and developed a cost savings analysis for each protocol used and helped to determine the best method for the company moving forward. The results concluded that the newly proposed method of injection offered a significant cost savings initiative, decreased site reactions, and still produced high immune response to maintain the expected rate of production.
Keywords: Sheep; Hyperimmunization; Polyclonal; Animal Health; Adjuvant; Agricultural Economics